2016
DOI: 10.1002/epi4.12015
|View full text |Cite
|
Sign up to set email alerts
|

Cannabis in epilepsy: From clinical practice to basic research focusing on the possible role of cannabidivarin

Abstract: SummaryCannabidivarin (CBDV) and cannabidiol (CBD) have recently emerged among cannabinoids for their potential antiepileptic properties, as shown in several animal models. We report the case of a patient affected by symptomatic partial epilepsy who used cannabis as self‐medication after the failure of countless pharmacological/surgical treatments. Clinical and video electroencephalogram (EEG) evaluations were periodically performed, and the serum levels of CBDV, CBD, and Δ9‐tetrahydrocannabinol were repeatedl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
44
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

4
5

Authors

Journals

citations
Cited by 32 publications
(47 citation statements)
references
References 15 publications
2
44
0
Order By: Relevance
“…This current rundown was mitigated by pretreatment of 2 hours with endogenous factors, as BDNF, or exogenous agents, as the cannabis derivative cannabidivarine (CBDV, Fig. 2D; Table S3) showing again a strong similarity with data previously published for MTLE patients 5,11 …”
Section: Resultssupporting
confidence: 71%
“…This current rundown was mitigated by pretreatment of 2 hours with endogenous factors, as BDNF, or exogenous agents, as the cannabis derivative cannabidivarine (CBDV, Fig. 2D; Table S3) showing again a strong similarity with data previously published for MTLE patients 5,11 …”
Section: Resultssupporting
confidence: 71%
“…However, these results do not fully explain the CBDV strong anti-convulsant efficacy shown in the preclinical models of epilepsy. Notably, in a recent paper [35] it has been shown that CBDV could act, as for CBD, on GABA A Rs modulating its function. In fact, CBDV was able to significantly recover the GABAergic "run-down" phenomenon [65] in a TRPV-independent manner, probably linked to intracellular processes of phosphorylation/dephosphorylation on GABA A Rs [35].…”
Section: Cannabinoids and Gaba A Rsmentioning
confidence: 99%
“…We then investigated the possible mechanism of action of EPO on GABAergic transmission, using staurosporine, a kinase blocker that binds to many kinases with a very low selectivity (Rüegg and Burgess, 1989). Our results clearly showed that EPO effect is indeed linked to a phosphorylation, but likely not due to the isoforms of PKC that are blocked by GF (PKC α, β1,δ, ζ) (Morano et al, 2016). Further experiments will better elucidate this point.…”
Section: Discussionmentioning
confidence: 87%